Multipoint problem for differential equations with partial derivatives with variable coefficients - Клюс, І.С. (Proceedings of National Aviation University, 2006)
The correctness of a problem with multi–point conditions on temporary variable of partial differential equations not solved as to the highest derivative with respect to time is investigated. The conditions of existence and uniqueness of the solution of a problem are established. The metric theorems of an estimations from below of small denominators that appears in constructing a solution of a problem are proved.